STRATEGI PEMERINTAH DESA KEDATON DALAM PEMBERDAYAAN MASYARAKAT MELALUI BADAN USAHA MILIK DESA KECAMATAN KALIANDA LAMPUNG SELATAN - Arifin, Bi'; Anwar, Anwar; Supraptiningsih, Supraptiningsih (Universitas Muhammadiyah Lampung, 2024)
ABSTRACTThe presence of village-owned enterprises is expected to have a positive impact on development and boost the village economy. Therefore, to ensure BUMDes operate effectively and in accordance with applicable regulations, the district government provides its support to the village government by allocating funds to the government. As a first step in starting BUMDes, this indicates that BUMDes are currently at the basic stage. In fact, there are still many village-owned enterprises that have not run as they should. Because there are several problems that hinder the running of BUMDes, one example is the willingness of villages that are less serious about BUMDes. The research method used is qualitative research, which is an analysis based on data obtained through interviews, observations, and documentation. The result of this study is the Kedaton Village Government Strategy in Community Empowerment through Village-Owned Enterprises in Kalianda District, South Lampung, based on three strategies: formulating, implementing, and evaluating.Keywords : Strategy, Government, Village, BUMDes